studying the effect of smoking on corneal endothelial cells - يوسف حبيب; كيال عمار (Latakia University Journal -Medical Sciences Series, 2021)
Purpose: to study the effect of smoking on corneal epithelial cells Methods: In this cross-sectional study, 180 eyes of 90 chronic smokers (smoker group) and 320 eyes of 160 age-matched, healthy non-smokers (non-smoker group) were enrolled. Corneal endothelial cells were evaluated by non-contact specular microscopy and photographed for analysis of cell density and hexagonality and the coefficient of variation in cell size and corneal central thickness. Results: Totally, 520 eyes of 260 patient were enrolled in the study (192 male,328 female), No statistically significant difference was found in the mean CCT, mean endothelial cell density, mean Cell area and endothelial cell size between smokers and non-smokers (P=0.7,P=0.5,P=0.07,P=0.1) . However, a lower percentage of endothelial hexagonal cells were observed in heavy smokers (48.6±4.3) than non-smokers (58.5±2.4) (P=0.0001). Conclusion: Our results suggest that cigarette smoking seems to affect the hexagonal cells of the corneal endothelium.